Methicillin-resistant Staphylococcus aureus in horses and horse personnel: An investigation of several outbreaks - van Duijkeren, E.; Moleman, M.; Sloet van Oldruitenborgh-Oosterbaan, M.M.; Multem, J.; Troelstra, A.; Fluit, A.C.; van Wamel, W.J.B.; Houwers, D.J.; de Neeling, A.J.; Wagenaar, J.A. (Veterinary microbiology, 2010)
At the Veterinary Microbiological Diagnostic Center, the Netherlands, the percentage of methicillin-resistant Staphylococcus aureus (MRSA) isolates found in equine clinical samples increased from 0% in 2002 to 37% in 2008. MRSA of spa-type t064, belonging to MLST ST8 and spa-types t011 and t2123, both belonging to the livestock-associated MLST ST398, predominated. During an outbreak of post-surgical MRSA infections in horses at a veterinary teaching hospital in 2006/2007, MRSA isolates of spa-type t2123 were cultured from 7 horses and 4/61 personnel which indicated zoonotic transmission. After intervention the outbreak stopped. However, another outbreak occurred in 2008, where 17 equine MRSA isolates of spa-type t011 ( n = 12), t2123 ( n = 4), and t064 ( n = 1) were found. This time, 16/170 personnel were positive for MRSA with spa-type t011 ( n = 11) and t2123 ( n = 5). Personnel in close contact with horses were more often MRSA-positive (15/106) than those without (1/64). Screening of horses upon admission showed that 9.3% were MRSA-positive predominantly with spa-type t011. Weekly cross-sectional sampling of all hospitalized horses for 5 weeks showed that 42% of the horses were MRSA-positive at least once, again predominantly with spa-type t011, which suggests that nosocomial transmission took place. Fifty-three percent of the environmental samples were MRSA-positive, including samples from students’ and staff members’ rooms, and all were spa-type t011. This indicates that humans contribute to spreading the organism. Culturing of samples employing high-salt pre-enrichment performed better than a comparable method without pre-enrichment. Our results show that nosocomial transmission occurs in equine clinics and suggests that personnel play a role in the transmission.